FEATURES OF PERFORMANCE AND POSSIBLE COMPLICATIONS OF IMMEDIATE DENTAL IMPLANTATION UNDER COMPLEX ANATOMICAL CONDITIONS - Yatsenko, P.I.; Chemerys, V.V.; Toropov, O.A.; Lychman, V.O.; Avetikov, D.S. (World of Medicine and Biology, 2025)
Dental implantation is one of the most advanced methods of restoring missing teeth. Depending on the timing of implant placement after tooth extraction, immediate and delayed dental implantation are distinguished. Delayed dental implantation is a classical approach, involving the placement of a dental implant 4 to 6 months after tooth extraction. Immediate dental implantation refers to the placement of the implant directly after the extraction procedure. This literature review examines techniques for immediate dental implantation in cases with complex anatomical conditions and analyzes possible complications that may arise both intraoperatively and in the long-term postoperative period.
Keywords: dental implantation; complex anatomical conditions; tooth extraction; bone plastic; adentia